Pengelolaan Risiko Kredit Atas Objek Jaminan Fidusia Berupa Hewan Ternak - Ugi Sugih Arto (Res Judicata, 2018)
This thesis, entitled “Credit Risk Management for Fiduciary Collateral Objects in the Form of Livestock” by using juridical normative type of research, which focused on the application of the rules and/or norms in positive laws that applies. With Bank’s effort on how to minimized the credit risk of the collateral objects in the form of livestock and bank’s effort if the collateral objects in the form of livestock are gone as the formulation of the problem which produced in this research. On practice, this type of credit is given to various type of businesses including livestock business. One of them is the type of business engaged on cattle breeding through cattle breeding credit scheme with subsidized interest. By its character, livestock can be classified as a fiduciary collateral in inventory. In general, the credit given by bank should be based on faith of debitor’s ability to repay their debts, and must be done by the principle that doesn’t harm the bank’s prominence, client as the debitor, and the depositors. This must be done, considering the credit given by the bank contain risks.